Trajectories of precariousness of tuk-tuk drivers in Portugal: A case study - Isabel Roque; Renato Miguel do Carmo; Jorge Caleiras; Rodrigo Vieira de Assis (Work Organisation, Labour and Globalisation)
In the aftermath of the Great Recession, the gig economy expanded in Portugal as an alternative form of income generation to overcome the accumulation crisis, especially in the tourism sector. One component of this, less well studied than platform labour in the delivery and accommodation sectors, was the introduction of tuk-tuks, or auto-rickshaws for passenger transport, using a hybrid business model combining a face-to-face approach on the streets, the use of internet websites that function as marketplaces, and digital platforms which connect them to the demand and supply of labour for other forms of local transport. Tuk-tuk drivers can experience precariousness, uncertainty, informality and intermittence and generally work as (bogus) independent workers. Drawing on in-depth and follow-up interviews, conducted between 2019 and 2020, this article aims to understand the structure of this service and to analyse the tuk-tuk drivers’ occupational trajectories in Portugal. It concludes that these workers are trapped in a permanent condition of precariousness, with continuous reinforcement of trajectories of vulnerability and suffering.